THE EFFECT OF MUSIC THERAPY AT THE CELLULAR AND TISSUE LEVEL: THE CONSISTENCY OF IBN SINO'S VIEWS AND MODERN HISTOLOGY (Universal International Scientific Journal, 2026)
This article analyzes the effects of music therapy on the human body at the cellular and tissue levels from a histological and physiological perspective. As a theoretical basis for the study, Abu Ali Ibn Sina's views on the therapeutic value of music and sound, as set forth in his works "The Canons of Medicine" and "The Book of Healing", were studied. Based on scientific studies indexed in modern PubMed and Scopus databases, the effects of music therapy on the central nervous system, neuroplasticity, stress hormones, and immune system cells were highlighted. The results of the study demonstrate the compatibility of Ibn Sina's views with modern histological studies and justify the possibilities of introducing music therapy into clinical practice.
Keywords: Music therapy; histology; neurophysiology